Nitrogen-Sulfur Co-Doped Reduced Graphene Oxide-Nickel Oxide Nanoparticle Composites for Electromagnetic Interference Shielding - Kumar, Rajesh; Macedo, Wagner C. [UNESP]; Singh, Rajesh K.; Tiwari, Vidhu S.; Constantino, Carlos J. L. [UNESP]; Matsuda, Atsunori; Moshkalev, Stanislav A. (Amer Chemical Soc, 2019)
The present work demonstrates the microwave -assisted synthesis of two different structural morphologies containing nickel oxide nanoparticles (NiO NPs) embedded in nitrogen (N) and sulfur (5) co-doped reduced graphene oxide (NS-rGO) nanosheets. The synthesized NiO anchored on NS-rGO nanosheets (NS-rGO-NiO composites) and NiO covered by NS-rGO nanosheets (NS-rGO:NiO composites) were used as an application in electromagnetic interference (EMI) shielding effectiveness (SE). The EMI SE studies reveal that NS-rGO:NiO composites show improved performance as compared to NS-rGO-NiO composites. In NS-rGO:NiO composites, the covered surface of NiO NPs by conducting NS-rGO nanosheets helps to improve the EMI SE application. The synthesized composite materials were extensively characterized using various techniques including scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction, thermogravimetric analysis, Raman spectroscopy, and X-ray photoelectron spectroscopy. Binding energy of N/S element in rGO nanosheets were analyzed by XPS and it is confirmed that the N atoms were present in three states in carbon skeleton of NS-rGO nanosheets as pyridinic, pyrrolic, and graphitic states; however, S atoms were present in single state as C S C configuration. The as synthesized NS-rGO:NiO composites reveal good performance for EMI applications and demonstrate the SE value of more than-,21 dB at thickness of 1.1 mm film of NS-rGO:NiO composites in microwave X-band range (8.2-12.4 GHz).
Keywords: N-S co-doped rGO; rGO covered nanostructures; metal nanoparticles; microwave; electromagnetic interference shielding